Applications of Surface Discharge Modeling, Simulation and Testing to Electrical Insulation Systems - (:unkn) unknown (My University, 2023)
Advances in power electronics and the increasing demand for highly power dense power distributionsystems have increased the demands for electrical insulation systems. A critical challenge in insulation system design is the prevention and mitigation of partial discharge which drives premature aging and failure of electrical assets. This work applies and validates a recently proposed model for surface discharge applied to the case of a laminated bus bar. The results from the modeling and testing shows the traditional concept of creepage, while essential for preventing a flashover events provides little insight into surface discharge. The approach to characterize the laminated bus bar provides insight into producing partial discharge free designs as a result of modeling. However, in many applications various stresses and conditions could result in partial discharge inception during the assets life, even if partial discharge is not present at commissioning. This motivates the selection of a candidate material which can endure partial discharge to some extent. In this pursuit an approach for rapid material characterization is explored through the testing of commercially available Corona Resistant Kapton (Kapton CR) and Non-Corona Resistant Kapton (Kapton NCR).
Keywords: Dynamic Health Index; Laminated Bus Bar; Partial Discharge; Surface Discharge; Surface Erosion